Investigation of the solid/liquid phase transitions in the U–Pu–O system. (March 2023) - Fouquet-Métivier, P.; Martin, P.M.; Manara, D.; Dardenne, K.; Rothe, J.; Fossati, P.C.M.; Guéneau, C.
Abstract: Mixed oxides of uranium and plutonium U1-y Puy O2-x are currently studied as reference fuel for Sodium-cooled Fast Reactors (SFRs). To predict the margin to fuel melting, an accurate description of both solidus and liquidus temperatures of these materials is crucial. In this work, after a critical review of the literature data, the parameters of the liquid phase of the CALPHAD models of the Pu–O and U–Pu–O systems are reassessed based on the model of Guéneau et al.. A good agreement between the calculated and selected experimental data is obtained. Using this model, the melting behaviour of U1-y Puy O2±x oxides is then studied as a function of plutonium content and oxygen stoichiometry. The congruent melting for the mixed oxides is found to be shifted towards low O/M ratios compared to the end-members (UO1.97 and PuO1.95 ). The temperature of this congruent melting is nearly constant (3130–3140 K) along a ternary phase boundary from UO1.98 to U0.55 Pu0.45 O1.82 and then decreases with Pu content to a maximum of approximately 3040 K for PuO1.95. This observation is explained by the stabilisation of the hypo-stoichiometric mixed oxides due to the increase of the configurational entropy at high temperatures by the formation of oxygen vacancies and related cation mixing. The influence of the atmosphere used in the laser heating melting experiments on the oxygen stoichiometry of the sample and its solidus and liquidus temperatures is investigated. The determination of this O/M ratio after laser melting tests using XANES is also reported. The simultaneous presence of U 6+, U 5+, U 4+, Pu 3+ and Pu 4+ is observed, highlighting the occurrence of charge compensation mechanisms. The samples are highly oxidised in air whereas close to stoichiometry (O/M = 2.00) in argon. These results are in agreement with the computed solidification paths. This work illustrates the complex melting behaviour of the U1-y Puy O2±x fuels and highlights the need for the CALPHAD method to accurately describe and predict the high-temperature transitions of the U–Pu–O system. Highlights: New CALPHAD models of the liquid phase of the Pu–O and U–Pu–O systems are developed. Cationic distributions and O/M ratios of molten samples were determined by XANES. A congruent-melting line is predicted for O/M < 2.00 with the stabilisation of the oxide. The formation of oxygen vacancies and the reduction of plutonium stabilises the oxide. The O/M ratio evolution is described during cooling from the melt to room temperature.